THE IMPORTANCE OF FUNCTIONAL TRAINING IN MOTOR DEVELOPMENT AND OVERWEIGHT AND OBESITY REDUCTION AMONG CHILDREN (Fiep Bulletin - online, 2017)
In light of the technological advance we have today, it is common to see people who do not practice any physicalactivities due to the practicalities that technology provides, reducing efforts that were once considered normal. Thus, habitsperformed by adults are passed on to children, causing them to also reduce the amount of movements performed, which areessential for motor development, leading to an increasing in overweight and obesity at this stage. In our research, we sought toshow the importance of functional training in childhood and the acquisition of motor skills, besides helping reduce the rates ofoverweight and obesity among children. According to Dias (2011) and Monteiro & Evangelista (2012), functional training refers toa set of exercises performed with the objective of working the skills used by the practitioner in their daily life, using integratedmovements and mobilization of more than one segment. At the same time, performed in different planes, involving differentmuscular actions. Understanding that motor development is the change in lifelong motor behavior and a process that begins withconception and ends with decease, the practice of functional training stimulates the development of motor skills and the variablesof physical fitness can be worked out in a balanced way, improving posture, strengthening muscles, bones and tendons,increasing the range of motor skills due to the variation of stimuli. Finally, new research should be carried out to emphasize theimportance that the practice of functional training can bring to children. Likewise, it is important to highlight that the practice ofphysical activities should be guided by properly trained professionals and appropriately followed exercises, which are necessaryfor the motor development of the children and inciting the practice of physical activity, increasing the chances of becoming moreactive adults.
Keywords: Functional Training; Motor Development; Child.